Public Private Partnership (PPP) in Forest Sector in Eastern Africa. Synthesis of Primary and Secondary Production Actors, and Trade - Kiplongei Cheboiwo, Joshua; Hussein Nasroun, Tageldin; Mwamakimbullah, Reuben; Kambugu Kyeyune, Robert; Mutaganda, Amini (Journal of Economics and Sustainable Development, 2018)
Kenya Forestry Research Institute (KEFRI) and partners with support from African Forest Forum undertook a study 2016 to evaluate the potential roles of the private sector in development of primary and secondary forest production in 10 countries in Eastern Africa. The main objective of the study was to provide information to support the emergence of organized private sector for sustainable forest management and enhanced livelihoods. The study involved literature reviews and some rapid reconnaissance surveys in key areas to facilitate updating of information and data especially in areas where gaps existed. Results indicate that primary forest production in Eastern Africa takes place in public natural forests, plantations, farm forests, community forests and private forests. These forests are facing heavy pressure from anthropogenic processes mostly conversion to agriculture, overgrazing, settlements and roundwood extractions. The indigenous forests and woodlands are the most extensive and produce wide range of products for various uses including timber and woodfuel among others. The public sector dominates ownership of indigenous forests and plantations forests whereas woodlands are owned largely by communities. In the last two decades private investors are entered into plantation forest sector with profit oriented motives, mostly in Uganda and Tanzania through issuance of leaseholds and permits. In the mix are private agricultural based enterprises such as tea estates, farmers, investment syndicates, social entrepreneurs and other entities that have also invested in plantation forests largely driven by the high demand for forest products and good returns to investment. Except for farm and private forests other types of forests are declining in either coverage and quality or both. Key plantation species include Eucalyptus, Pinus, Cupressus lusitanica, Tectonia grandis and Gmelina arborea among others. In the drier ecosystems are dominated by Acacias, Balanites, commiphora, Anogiessus leiocarpus, Albizia amara, and Acacia senegal. The wood based industries include saw mills, reconstituted wood, furniture making, transmission pole treatment plants, wood carving and charcoal production. Processing and value adding industries produce a wide range of such as sawnwood, fibre boards, particle boards, plywood, furniture, biomass energy, fuel pellets, handcrafts and wooden poles among others. The non-timber products produced in the region include myrrh, baobab fruits, tannins, tamarinds, Aloes, shea butter, plant tannins, medicinal plant parts, and gum arabic among others. The public forest resources in the region are managed by lead public forest such as Kenya Forest Service (KFS) in Kenya, Forest National Corporation (FNC) in Sudan, and Tanzania Forest Service (TFS) in Tanzania, National Forest Authority (NFA) and Rwanda National Natural Resources Authority (RNNRA) in Rwanda. The public agencies are mandate on management, protection regulation and facilitation of private and individual forest owners.The technical and management organization in primary production include individual farmers, tree growers associations, (TGAs), community groups, investment syndicates, companies, and wood based industries. Technical and commercial organizations in secondary forest production include saw millers, furniture and wood manufacturers associations.The countries have enacted policies and legislations that have good provisions that support various private sector investors in establishment of commercial plantations and wood based manufacturing industries. Most countries in the region are not self-sufficient in various forest products and have to import from outside the region mostly Asia and Europe. Therefore the region provides opportunities for private investors with desired financial capital and operational efficiency to enter into both primary and secondary forest production in order to enhance forest sector contribution to regions overall socio-economic development.
Keywords: Forest production; Public private partnerships; Technical and management organizations; Trade in forest products